1617. Mecillinam susceptibility against Enterobacterales isolated from urinary tract infections from US patients in 2018. (31st December 2020) - Hawser, Stephen; Morrissey, Ian; Charrier, Cedric; De Piano, Cyntia; Alexander, Morton; Henriksen, Anne Santerre
Abstract: Background: Mecillinam is a unique amidinopenicillin antibiotic, being the first and the only compound in its class. In contrast to other beta-lactams, it has a unique mechanism of action whereby it exerts its antibacterial activity through binding to penicillin binding protein 2. Pivmecillinam is the oral-prodrug of mecillinam and recommended as a first line therapy in the IDSA guidelines for uncomplicated urinary tract infections (uUTI), despite not yet being available in the USA. To support the clinical development of mecillinam and pivmecillinam in the USA for the treatment of both complicated UTI and uUTI this study investigated the activity of mecillinam against Enterobacterales isolates from the USA during 2018. Methods: A total of 1, 090 isolates from urinary tract infections from patients in the USA were tested. Activity of antibiotics was tested by CLSI methodology and susceptibility interpreted according to CLSI guidelines. Results: Susceptibility and activity of each antibiotic are shown in the Table. Mecillinam MIC50 and MIC90 were 0.25 and 4 µg/mL, respectively and 94.5% of isolates were susceptible. Fosfomycin MIC50 and MIC90 were 2 and 32 µg/mL, respectively and 95.7% of isolates were susceptible. The other four comparator antibiotics showed MIC90 values >8 µg/mL and a 70.5 – 79.9% susceptible isolates. The highest MIC90 against all isolates combined was 64 µg/mL for nitrofurantoin and the highest percentage of resistance was obtained with trimethoprim-sulfamethoxazole with 29.5%. Resistance towards ceftriaxone and ciprofloxacin was 19.6% and 26.1%, respectively. Table Conclusion: Overall, mecillinam showed the lowest MIC90 and a comparable susceptibility profile (94.5 % susceptible and 4.0 % resistant) to fosfomycin (i.e. 95.7% and 2.0% resistant) susceptible isolates). Resistance to ceftriaxone, ciprofloxacin and trimethoprim/sulfamethoxazole around or above 20% is concerning for their clinical usage to treat urinary tract infections. These encouraging susceptibility data warrant further studies to support the clinical development of mecillinam/pivmecillinam for the treatment of UTI in the USA. Disclosures: Stephen Hawser, PhD, Tetraphase Pharmaceuticals (Scientific Research Study Investigator) Cedric Charrier, PhD, IHMA (Employee)Utility Therapeutics (Independent Contractor) Cyntia De Piano, PhD, IHMA (Employee)Utility Therapeutics (Independent Contractor) Morton Alexander, PhD, Utility Therapeutics (Employee, Shareholder) Anne Santerre Henriksen, MS, Maxel Consulting ApS (Employee)Utility Therapeutics (Independent Contractor)